2016
DOI: 10.3389/fimmu.2016.00202
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of HLA-DP/DQ and ICAM-1 SNPs among Ovarian Cancer Patients

Abstract: BackgroundOvarian cancer is one of the most lethal gynecological malignancies and the fifth leading cause of cancer deaths among women. The high mortality rate is largely attributed to its diagnosis in advanced stages. Poor prognosis of ovarian cancer is usually due to the lack of specific or effective screening and diagnostic methods for identifying early-stage disease.AimOur study aimed to study the role of HLA-DP, HLA-DQ, and ICAM-1 SNPs in diagnosis and/or prognosis of ovarian tumorsSubjects and methodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…This suggests that these MHC class II molecules have an important effect on the mechanism underlying cancer chemoresistance. This result was in agreement with other studies, which found that the MHC complex played a main role in ovarian immunology and that both HLA class I and II molecules contributed to resistance to treatment [15,16]. This result was further validated by the TCGA database, which predicted that patients with high expression of HLA-DPA1 would be more CR to initial chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that these MHC class II molecules have an important effect on the mechanism underlying cancer chemoresistance. This result was in agreement with other studies, which found that the MHC complex played a main role in ovarian immunology and that both HLA class I and II molecules contributed to resistance to treatment [15,16]. This result was further validated by the TCGA database, which predicted that patients with high expression of HLA-DPA1 would be more CR to initial chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…MHC class II antigen DP Alpha 1 ( HLA-DPA1 ) is a MHC class II paralogue. Single nucleotide polymorphisms within HLA-DP have been significantly associated with OVCA incidence and increased tumor aggressiveness [ 22 ]; therefore, we selected this locus to evaluate. Treatment with azacytidine or entinostat resulted in significant increases in HLA-DPA1 expression relative to the vehicle group (p = 0.0135 and 0.0053, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest was the antigen processing and presentation pathway, in which we were able to identify several high‐impact mutations in our cohort in genes including HLA‐DRB5 and HLA‐DRB1 . Human leukocyte antigen (HLA)‐class I and II haplotypes have been associated with the pathogenesis of ovarian and breast cancer (Ghazy & El‐Etreby, ). It would be prudent to determine what truncations are being held in the HLA class I and II genes that cross reference with other databases such as the Human Gene Mutation Database.…”
Section: Commentarymentioning
confidence: 99%